Guillain-Barre Syndrome following COVID-19 Infection: First Case Report from Kuwait and Review of the Literature - Kamel, Walaa A. (Dubai Medical Journal, 2021)
OBJECTIVE: Guillain-Barré syndrome (GBS) is an acute immune-mediated polyradiculoneuropathy that is often related to a previous infectious exposure. GBS emerged as a potentially serious complication of coronavirus disease 2019 (COVID-19) since its declaration as a global pandemic. We report the first case from Kuwait, to the best of our knowledge. CLINICAL PRESENTATION: A 72-year-old male presented with 3 weeks history of acute progressive and ascending lower limbs weakness. He developed these symptoms 3 weeks after testing positive to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Electrophysiological studies showed acute demyelinating polyradiculoneuropathy and cerebrospinal fluid showed protein-cell dissociation. He was successfully treated with intravenous immunoglobulins (IVIGs). CONCLUSION: Neurologists should be aware of GBS as a potentially serious complication associated with COVID-19. Our patient had a favorable outcome with IVIG with no autonomic or respiratory affection.